1997
DOI: 10.1002/(sici)1096-8644(199705)103:1<69::aid-ajpa5>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope ratios indicate diet and habitat use in New World monkeys

Abstract: This paper demonstrates the use of stable isotope ratios of carbon and nitrogen in animal tissues for indicating aspects of species behavioral strategy. We analyzed hair from individuals representing four species of New World monkeys (Alouatta palliata, the mantled howler; Ateles geoffroyi, the spider monkey; Cebus capucinus, the capuchin; and Brachyteles arachnoides, the woolly-spider monkey or muriqui) for d 13 C and d 15 N using previously developed methods. There are no significant differences in either ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 59 publications
4
78
0
1
Order By: Relevance
“…When adjusted for tissue type (δ 13 C keratin values were adjusted by +2‰ (15) for comparability with δ 13 C coll values), average chimpanzee δ 13 C values (−22.9 ± 0.5‰) reflect their regular consumption of fruit and are similar to those reported for the Ganta chimpanzee collection from neighboring Liberia (23). However, both males and females had δ 15 N values higher than 7‰, which indicates a level of dietary protein higher than could be obtained from fruit alone, suggests some level of insectivory or carnivory (17,18,23,24).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…When adjusted for tissue type (δ 13 C keratin values were adjusted by +2‰ (15) for comparability with δ 13 C coll values), average chimpanzee δ 13 C values (−22.9 ± 0.5‰) reflect their regular consumption of fruit and are similar to those reported for the Ganta chimpanzee collection from neighboring Liberia (23). However, both males and females had δ 15 N values higher than 7‰, which indicates a level of dietary protein higher than could be obtained from fruit alone, suggests some level of insectivory or carnivory (17,18,23,24).…”
Section: Resultsmentioning
confidence: 96%
“…Previous research on unsexed (16,24) and sexed (23) chimpanzees, habituated sexed bonobos (12), and other primate species (17,18) indicated that significant sex differences in adult δ 13 C and δ 15 N are unlikely. We found no significant sex differences in δ 13 C in the Taï chimpanzees; however, our δ 15 N values support behavioral observations of significant meat eating among some adult males at Taï compared with adult females and juveniles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the δ 13 C of herbivores feeding here reflect proportions of C 3 to C 4 /CAM biomass consumed. Stable nitrogen isotopes ( 15 N/ 14 N, or δ 15 N) are influenced by a more complex combination of environmental parameters, but used in conjunction with δ 13 C offer additional insights into trophic position, diet, dietary quality, and ecophysiology (Ambrose 1991;Robbins et al 2005;Schoeninger et al 1997;Sealy et al 1987;Sponheimer et al 2003a). An added benefit of isotopic tools is that one documents diet over different time scales.…”
Section: Introductionmentioning
confidence: 87%